2018
DOI: 10.1016/j.neuropharm.2018.02.026
|View full text |Cite
|
Sign up to set email alerts
|

AMPA receptor GluA1 Ser831 phosphorylation is critical for nitroglycerin-induced migraine-like pain

Abstract: Migraine is the third most common disease worldwide; however, the mechanisms underlying migraine headache are still not fully understood. Previous studies have demonstrated that α-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid (AMPA) receptor phosphorylation plays an important role in central sensitization of pain transmission. In the present study, we observed that AMPA receptor GluA1 Ser831 phosphorylation was enhanced in the spinal trigeminal nucleus caudalis (Sp5C) after intraperitoneal injection of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 69 publications
1
25
0
Order By: Relevance
“…In this study, we focused on the comorbid myogenic TMD and migraine-like hypersensitivity. A systemic injection of NTG has been used extensively to induce migraine-like hypersensitivity [17][18][19][20]43]. Our results are consistent with these previous studies: 10 mg/kg of NTG induces acute periorbital hypersensitivity, while 1 mg/kg of NTG is not enough to induce significant hypersensitivity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we focused on the comorbid myogenic TMD and migraine-like hypersensitivity. A systemic injection of NTG has been used extensively to induce migraine-like hypersensitivity [17][18][19][20]43]. Our results are consistent with these previous studies: 10 mg/kg of NTG induces acute periorbital hypersensitivity, while 1 mg/kg of NTG is not enough to induce significant hypersensitivity.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that masseter muscle tendon ligation (MMTL) in rats can produce myogenic TMD pain [15,16] and that systemic injection of nitroglycerin (NTG) can induce acute migraine-like hypersensitivity [17][18][19][20]. An essential role for calcitonin gene-related peptide (CGRP) has been indicated in migraine pathophysiology [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The pain hypersensitivity in the periorbit and hind paw produced by NTG injection corresponds to the cutaneous allodynia of the cephalic and extracephalic region in patients with CM [54,78]. Furthermore, NTG treatment also elicits some migraine-speci c symptoms in mice, comprising photophobia, hypoactivity, and facial grimace behaviors, which are similar to the characteristics of photophobia and activities aggravating headache in patients with CM [79][80][81].…”
Section: Discussionmentioning
confidence: 78%
“…The pain hypersensitivity in the periorbit and hind paw produced by NTG injection corresponds to the cutaneous allodynia of the cephalic and extracephalic region in patients with CM [32]. Furthermore, NTG treatment also elicits some migraine-speci c symptoms in mice, comprising photophobia, hypoactivity, and facial grimace behaviors, which are similar to the characteristics of photophobia and activities aggravating headache in patients with CM [45,46]. Central sensitization is an abnormal state of increased responsiveness of the nociceptive system, which is caused by the enhanced excitability of neurons and circuits in the nociceptive pathway [39].…”
Section: Discussionmentioning
confidence: 80%